Integrative advisory services : expanding your accounting services beyond the cloud - Vetter, Amy, 1974- (Wiley, 2017)
Stop crunching numbers and start truly serving your clients Integrative Advisory Services is the CPA, accounting professional and bookkeeper's guide to the future. As technology paves the way for increased self-reliance and DIY financial services, much of the traditional data entry tasks of accounting professionals and bookkeepers will be reduced. Yet, nothing can replace the human side of the client-advisor experience and the desire to improve your clients' businesses with financial information. Technology will continue marching on, so accounting professionals must adapt to the changing marketplace to thrive in this new paradigm. This book shows you how to provide the kind of value that technology cannot: human connection. Rather than simply reporting data, today's accounting professionals have an opportunity to take a much more active role in their clients' business by analyzing the story behind the numbers, understanding both operations and finance, and guiding the client toward the outcomes they need. Creating an ongoing relationship throughout the year allows you to be proactive rather than reactive, and help your client's business at a holistic level. Your business owner and CEO clients can get the numbers from the computer too'but, they come to you for personalized advice, explanations, and guidance based on their unique situation and financial needs. This book shows you how to take on more of an advisory role and become a critical component of your client's success.-Spend less time crunching numbers and more time advising clients -Become an integral part of the client's decision-making process -Provide real value by clearly communicating financial data analysis -Become the strategic partner your client cannot do without Cloud technology, machine learning, and artificial intelligence are not the death knell for financial advisors; in fact, they're the opposite'they do the number crunching for you, leaving you more time to provide the personal guidance that no computer could. As the financial advisory industry evolves, Integrative Advisory Services is your real-world guide to adapting and thriving.